Decorative frames a practicle guide to creative ideas - Innes, Miranda (Crafts library, 1995)
A practical guide to making and decorating frames for every room in the house, features projects in wood, metal, paper, and fabric, with explainations of many techniques, from decoupage to mosaics and marbling.